THE DEVELOPING TRANSPERSONNEL PSYCHOLOGY - Hendro Prabowo (Universitas Gunadarma, 2009)
The progress of transpersonal psychology is related to the other science. The most higher potention in understanding transpersonal psychology is in consciousness level. In Islam, it has been called as qolbu and fitrah, in Christian it has been called as spirit, and in Hindu it has been called as atman. There is no differences in the terminology of transpersonal and spiritual. The connection condition that makes us related one to another can be explained also in quantum phsysics. This paper wants to describes the progress of transpersonal psychology and the other related things.Keywords: transpersonal psychology, Islamic psychology